Checklist of water mites from mainland Portugal and its archipelagos - Cantallo, Harold; Gomes, Nuno; Antunes, Carlos; Martins, Duarte; de Araújo Costa, Dimítri (Zootaxa, 2022)
This study focuses on aquatic mites from the Portuguese Exclusive Economic Zone, including the mainland area, and Madeira and Azores archipelagos, aiming at compiling all existing information and generating a list of species and all their data on collecting sites. For the present work, we consider aquatic species, those that inhabit the marine, deep sea, intertidal, freshwater, transition water or brackish environments, with life-cycle occurring entirely at water habitats or their vicinity. Furthermore, breeding should take place in water aquatic lifestyles. The dataset search for this checklist started with the first descriptions of water acarids from the Azores Archipelago performed by Théodore Barrois. Primary sources for occurrence confirmation were Süßwasserfauna von Mitteleuropa book collection, The Global Biodiversity Information Facility (GBIF), complemented with an extensive Portuguese literature review and data biodiversity websites, e.g., European Water Mite Research (Watermite.org). In total, 102 valid species were found belonging to 41 genera, and 19 families, nested in the orders Mesostigmata, Sarcoptiformes and Trombidiformes. This is the first work compiling all the species of aquatic mites found in Portuguese territory, as well as data of collection, serving as the basis for future studies.